(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Concrete is one of the oldest and most widely used building materials in the world, mostly because it is inexpensive and readily available. In all areas of contemporary construction, concrete has become a key component of structures. It is challenging to name another building material that is as versatile as concrete. When strength, durability, impermeability, fire resistance, and absorption resistance are needed, concrete is the ideal material to use. This study’s main goal is to compare plain M30 grade concrete to basalt fiber concrete in terms of compressive, flexural, and splitting tensile strength. Basalt fiber is a substance created from the incredibly tiny basalt fibers that naturally occur in volcanic rocks that are the result of frozen lava. In the aerospace and automobile industries, it is utilized as a fire-resistant textile. Fibers are typically added to concrete to strengthen its structural stability. Due to its remarkable qualities, such as resistance to corrosion and low thermal conductivity, basalt fiber is currently among the fibers that is gaining more prominence. Additionally, it increases the concrete’s toughness, flexural strength, and tensile strength. Important concrete constructions like nuclear power stations, roads, and bridges can employ it to prolong their lifespan. The variable factors taken into account in this study were M30 grade concrete cubes, cylinders, and beams, which were cast and cured in portable water for 28 days. The cubes’ dimensions were 150 x 150 x 150 mm, the cylinders’ dimensions were 150 mm (dia) x 300 mm (depth), and the beams’ dimensions were 500 x 100 x 100 mm. Then, at 7, 14, and 28 days, the specimens were examined for split tensile strength, flexural strength, and compression strength using ordinary concrete with and without basalt fiber.